(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In a democratic system, the media play a crucial role in educating the public about the policies and programs of various political groups. The media creates the public’s perception of political parties in addition to serving as a watchdog over society and reporting on politicians’ abuse of power. Public opinion was shaped in part by political campaigns that used many types of media, including print, electronic, and the internet. Information reaches the target audience via the ever-expanding reach of social media. There will be a larger youth population than in previous elections for both the legislature and the general assembly, and campaigns targeting this demographic will use social media as a weapon. This article investigates the effect that political parties’ usage of social media has on voters’ perceptions of such parties. The study explored the ways in which political parties use social media to spread their ideas and build their own reputations among their followers and the general public. Finding out how individuals see political discourse and campaigns on social media is another goal of the article. The purpose of this paper is to administer a survey to 400 people in the Jaipur area. More and more, people are able to put aside their differences and work together thanks to social media. In the present context, it serves as a horizontal communication medium that offers the advantages of participatory democracy. You can learn more about how social media will play a role in the next elections by reading this study. Furthermore, the article will assess how widespread the use of social media platforms is in political discourse.